Monitoring the West African heat low at seasonal and intra‐seasonal timescales using AMSU‐A sounder. (31st July 2013) - Lavaysse, C.; Eymard, L.; Flamant, C.; Karbou, F.; Mimouni, M.; Saci, A.
Abstract: The Saharan heat low (SHL) is defined as a stationary thermal depression below 700 hPa located over the Sahara during the boreal summer season. This feature has a significant impact on the seasonal and intra‐seasonal variability of rainfall over the Sahel. For various reasons, few observations are assimilated in operational numerical weather prediction models, especially surface sensitive observations. In this study we make use of the advanced microwave sounding unit (AMSU‐A) brightness temperatures measured at 52.8 GHz (noted A4 hereafter) and at 53.6 GHz (noted A5 hereafter) to detect the heat low and to characterize its intensity at the seasonal and intra‐seasonal scales. In terms of seasonal variability, AMSU‐based estimates of SHL are found in good agreement with those based on the European Center Medium‐range Weather Forecast ERA‐I reanalyses for the period ranging from 2000 to 2011. However, differences exist between the two datasets at intraseasonal timescale. They may be related to mismatches between the numerical weather prediction model levels and the level of maximum of sensitivity of the AMSU observations. Particular meteorological situations can also explain some differences between the two types of products, as there is a lack of assimilated observations in this region. Finally, we show that the A4 brightness temperature is a suitable proxy to provide a good estimate of the location and the intensity of the SHL from daily to seasonal timescales.